Personal Strategies on the Dynamics of Job Demands-Resources and Fatigue: A Latent Transition Approach - Manuel Pulido-Martos; Esther López-Zafra; Daniel Cortés-Denia (Journal of Work and Organizational Psychology)

(untitled)
Fatigue can lead to negative workplace consequences. Within a job demands-resources framework, this study examines: (a) latent profiles of job demands and job and personal resources, (b) associated fatigue levels, (c) profile stability over time, and (d) how job-crafting and self-undermining influence profile membership and transitions, impacting fatigue. Data was collected from Spanish employees at two time points (T1, n = 749; T2, n = 228) and analyzed using latent profile and latent transition approaches. Results revealed three stable profiles: (1) limited leadership resources and moderate workload, (2) moderate resources and moderate workload, and (3) high resources and moderate-high workload, with the latter showing lowest fatigue levels. Job-crafting predicted both maintenance of favorable profiles and transitions toward high-resource profiles. Self-undermining showed no significant effects. Findings highlight job crafting’s importance in maintaining beneficial resource-demand profiles that prevent workplace fatigue, suggesting organizations should promote job-crafting behaviors as effective fatigue management strategies.